2016
DOI: 10.1371/journal.pone.0157340
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization of a Panel of Diverse HIV-1 Isolates at Seven International Sites

Abstract: HIV-1 subtypes and drug resistance are routinely tested by many international surveillance groups. However, results from different sites often vary. A systematic comparison of results from multiple sites is needed to determine whether a standardized protocol is required for consistent and accurate data analysis. A panel of well-characterized HIV-1 isolates (N = 50) from the External Quality Assurance Program Oversight Laboratory (EQAPOL) was assembled for evaluation at seven international sites. This virus pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 40 publications
(34 reference statements)
1
12
0
Order By: Relevance
“…Thus, we retrieved a total of 80 contigs that were subtyped as follows: clade B (n = 20), CRF12_BF (n = 5), clade C (n = 8), clade D (n = 10), clade F2 (n = 5), clade G (n = 3), clade A1 (n = 10), CRF02_AG (n = 9) and CRF01_AE (n = 10). For majority of the sequences analyzed, the subtype assigned to the 5’LTR of the HIV-1 isolate was concordant with its previously reported primary genotype [ 44 46 , 52 ]. However, we found that additional contigs from 5 clade B specimens were subtyped as CRF12_BF (BF), one of the two contigs from a CRF02_AG (AG) specimen was assigned to be F2, and all the LTR sequences retrieved from the CRF22_01A1 (01A1) specimens were subtyped as CRF01_AE (AE) Table 2 .…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Thus, we retrieved a total of 80 contigs that were subtyped as follows: clade B (n = 20), CRF12_BF (n = 5), clade C (n = 8), clade D (n = 10), clade F2 (n = 5), clade G (n = 3), clade A1 (n = 10), CRF02_AG (n = 9) and CRF01_AE (n = 10). For majority of the sequences analyzed, the subtype assigned to the 5’LTR of the HIV-1 isolate was concordant with its previously reported primary genotype [ 44 46 , 52 ]. However, we found that additional contigs from 5 clade B specimens were subtyped as CRF12_BF (BF), one of the two contigs from a CRF02_AG (AG) specimen was assigned to be F2, and all the LTR sequences retrieved from the CRF22_01A1 (01A1) specimens were subtyped as CRF01_AE (AE) Table 2 .…”
Section: Resultssupporting
confidence: 82%
“…Sixty five high titer virus derived from de-identified plasma specimens obtained from DUKE EQAPOL viral diversity program [ 44 ], and five CRF02_AG virus isolated from stored and de-identified plasma specimens [ 45 47 ] as previously described [ 48 ] were selected for this study. The study was approved by the Duke University Institutional Review Board for clinical investigation (Pro0029507) and the Review Board of the US HHS/Food and Drug Administration Research in Human Subjects Committee (exempt reference number 01-044B).…”
Section: Methodsmentioning
confidence: 99%
“…To address this, well-characterized genetically diverse HIV clinical isolates assembled by the External Quality Assurance Program Oversight Laboratory (EQAPOL) were used to develop limit-of-detection (LOD) panels for assessment of the analytic sensitivities across platforms using p24 Ag-capture components, i.e., HIV fourth-generation diagnostic assays, stand-alone p24 Ag enzyme immunoassays (EIAs), novel p24 Ag digital detection technologies, and rapid point-of-care (POC) p24 Ag and Ab assays, relative to the analytic sensitivities of VL assays. Twenty isolates were selected from the EQAPOL Genotype Diversity Panel (19) to represent globally relevant subtypes and circulating recombinant forms (CRFs) and further characterized to confirm VL and p24 concentrations to ensure that the Ag/RNA ratios were consistent with the expected values (see Table S1 in the supplemental material). Both manufacturers and clinical and research labs participated in the comparison study ( Table 1).…”
mentioning
confidence: 99%
“…Samples were selected as being representative from geographically diverse origins as a subset of the EQAPOL Genetic Diversity Panel and characterized by nearly full-length genome sequencing for subtype and recombination pattern by single-genome amplification (SGA) at the EQAPOL core laboratory and phylogenetic analysis, as previously described (see Fig. S1 in the supplemental material) (19). This genetic characterization confirmed that gag region sequences were consistent with the genotype assignment (see the GenBank accession number assignments in reference 19).…”
mentioning
confidence: 99%
See 1 more Smart Citation